Rising Population and Economic Growth: The Role of Human Capital Development - Ifeacho, Christopher Ikechukwu (Acta Universitatis Danubius. Œconomica, 2025)
This study investigates the mediating role of human capital development in the relationship between rising population and economic growth in South Africa. Understanding this nexus is vital for policy formulation aimed at harnessing population growth as a driver of sustainable development. The research builds on demographic-economic transition theories and human capital-led growth literature. It extends the discourse by integrating the interaction between population dynamics and capital accumulation in the South African context. Using annual data from 1960 to 2023, the study employs the AutoRegressive Distributed Lag (ARDL) technique to analyse both short- and long-run relationships among variables. The findings reveal that physical capital formation significantly boosts economic growth in the short run. Population growth contributes positively to economic performance only when matched with human capital development. However, unchecked population growth without adequate investment in human capital negatively impacts growth. Inflation poses a consistent threat to growth, while trade openness exhibits both growth-enhancing and distortionary effects through labour market disruptions. The study offers valuable insights for policymakers, particularly in designing strategies for balanced capital investment, inflation control, and education reform to align with global market needs. The study uniquely demonstrates the conditional effect of population on growth via human capital, highlighting the importance of coordinated macroeconomic and educational policies in a developing economy.